Рятівні дослідження на Бродівщині у 2009 р. - Лазурко, О.Р.; Назар, І.І.; Сало, Б.Я.; Чорний, А.М. (Археологічні дослідження в Україні, 2010)
In 2009, the expedition of the Scientific and Research Centre of the Rescue Archaeological Service of the IA NASU conducted rescue archaeological research in Brody Region of Lviv Oblast at the area of oil pipeline construction. The most significant works were held at Zahirtsi I and V sites which incurred the hardest devastation.